HT-Paxos: High Throughput State-Machine Replication Protocol for Large Clustered Data Centers - Vinit Kumar; Ajay Agarwal (The Scientific World Journal)
Paxos is a prominent theory of state-machine replication. Recent data intensive systems that implement state-machine replication generally require high throughput. Earlier versions of Paxos as few of them are classical Paxos, fast Paxos, and generalized Paxos have a major focus on fault tolerance and latency but lacking in terms of throughput and scalability. A major reason for this is the heavyweight leader. Through offloading the leader, we can further increase throughput of the system. Ring Paxos, Multiring Paxos, and S-Paxos are few prominent attempts in this direction for clustered data centers. In this paper, we are proposing HT-Paxos, a variant of Paxos that is the best suitable for any large clustered data center. HT-Paxos further offloads the leader very significantly and hence increases the throughput and scalability of the system, while at the same time, among high throughput state-machine replication protocols, it provides reasonably low latency and response time.